2012
DOI: 10.1088/0264-9381/29/22/224009
|View full text |Cite
|
Sign up to set email alerts
|

Optical black hole lasers

Abstract: Using numerical simulations we show how to realise an optical black hole laser, i.e. an amplifier formed by travelling refractive index perturbations arranged so as to trap light between a white and a black hole horizon. The simulations highlight the main features of these lasers: the growth inside the cavity of positive and negative frequency modes accompanied by a weaker emission of modes that occurs in periodic bursts corresponding to the cavity round trips of the trapped modes. We then highlight a new regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
0
48
0
1
Order By: Relevance
“…Indeed, although the initial observations were made in the context of light propagation in optical fibre 1 , similar ideas have subsequently been explored also in other optical systems 3,9 . Of course, analogies should always be applied with care, as perturbative physical effects present in one system may not always possess a clear counterpart in the other.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, although the initial observations were made in the context of light propagation in optical fibre 1 , similar ideas have subsequently been explored also in other optical systems 3,9 . Of course, analogies should always be applied with care, as perturbative physical effects present in one system may not always possess a clear counterpart in the other.…”
Section: Discussionmentioning
confidence: 97%
“…This picture not only suggests interesting links with general relativity 1,3,4,8,9 , but the underlying dynamics have also been postulated to influence the formation of optical rogue waves 7,11,12 , and to allow for the realization of optical functionalities such as the all-optical transistor 5 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Among others, we can cite studies involving cross-phase modulation (XPM) effects [1][2][3][4], or four wave mixing processes [3][4][5][6][7]. Recently, it has been shown that some of these interactions can mimic, under some circumstances, the interactions occurring at the horizons of black and white holes [8][9][10][11]. These so-called optical event horizons occur when an intense pulse, propagating in a nonlinear waveguide, prevents a weak probe wave traveling at a different velocity from passing through it.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of geometry on wave propagation can be tracked back to Lord Rayleigh in the early theory of sound [1], and extend to recent investigation as, for example, analogs of gravity in Bose-Einstein condensates [2], optical event horizon in fiber solitons [3,4], Anderson localization [5], random lasing [6] and celestial mechanics in metamaterials with transformation optics [7][8][9][10]. In addition to linear optics in curved space [11], geometrical constraints affect shape preserving wave packets, including localized solitary waves [12], extended Airy beams [13], and shock waves [14,15].…”
mentioning
confidence: 99%